Nasal high-frequency oscillatory ventilation (nHFOV) versus nasal continuous positive airway pressure (NCPAP) as an initial therapy for respiratory distress syndrome (RDS) in preterm and near-term infants - Ramin Iranpour; Amir-Mohammad Armanian; Ahmad-Reza Abedi; Ziba Farajzadegan (BMJ Publishing Group, 2019)
Background Currently, various forms of non-invasive respiratory support have been used in the management of respiratory distress syndrome (RDS) in preterm neonates. However, nasal high-frequency oscillatory ventilation (nHFOV) has not yet been applied commonly as an initial treatment.Objectives This study was designed to investigate the efficacy and safety of nHFOV compared with nasal continuous positive airway pressure (NCPAP) in preterm and near-term infants with RDS.Methods In a randomised clinical trial, a total of 68 neonates (gestational age (GA) between 30 and 36 weeks and 6 days) with a clinical diagnosis of RDS were randomly assigned to either the NCPAP (n=34) or the nHFOV (n=34) group. The primary outcome was the duration of non-invasive respiratory support (duration of using NCPAP or nHFOV).Result The median (IQR) duration of non-invasive respiratory support, was significantly shorter in the nHFOV group than that in the NCPAP group (20 (15-25.3) versus 26.5 (15-37.4) hours, respectively; p=0.02). The need for a ventilator occurred in 4 out of 34 (11.8%) neonates in the NCPAP group and in none of the neonates in the nHFOV group (p=0.03). In addition, intraventricular haemorrhage (IVH) occurred in nine cases (6.9%) in the NCPAP group and two cases (3.3%) in the nHFOV group, which showed a significant difference (p=0.04). The incidence of pneumothorax, chronic lung disease, pulmonary haemorrhage and necrotising enterocolitis was similar between the two groups.Conclusion This study showed that nHFOV significantly reduced the duration of non-invasive respiratory support and decreased the need for intubation compared with NCPAP in infants with RDS. Furthermore, nHFOV seems to reduce the incidence of IVH without increasing other complications.Trial registration number IRCT2017062734782N1.